Réponses

2014-10-24T10:35:53+02:00
A= -74+15-13
A= -59-13
A= -72

D= -15+19+48+68
D= 4+48+68
D= 120

E = -5+29+68+68
E= +24 + 68 + 68
E= ........

B = -25 -100 -15
B = -125-15 =   -14 0

D=  -31,5 +7,5+0,5-3,5
D = -24 +0,5-3,5
D = -23,5-3,5 = -27

F=-19,5 +7,5+0,5-3,5
F = -12 +0,5 -3,5
F = -11,5 -3,5
F = -15
2014-10-24T10:38:59+02:00
A=(-74)+(+15)+(-13)
= -72

D=(-15)-(-19)-(-48)-(-68)
= -15 + 19 + 48+ 68
= 120

E=(-5)-(-29)-(-68)-(-68)
 = -5 + 29 + 68 + 68
 = 160

B=(-25)+(-100)+(-15)
 = -25 -100 -15 
= 140

D=-27-4,5+7,5-(-0,5)+(-3,5)
 = -27 -4,5 + 7,5 + 0,5 - 3,5
= - 27,4

F=-15-4,5+7,5-(-0,5)+(-3,5)
= -15 - 4,5 + 7,5 + 0,5 - 3,5
= -15